GAMBARAN KOMPLIKASI PASCA SPINAL ANESTESI DENGAN SUB ARACHNOID BLOCK (SAB) DI RS KHUSUS BEDAH JATIWINANGUN - Ais Asri Sanubari. NM; Made Suandika; Amin Sutanto (Journal of Nursing and Health, 2024)
Introduction The incidence of spinal anesthesia is increasing worldwide, according to WHO data showing that around 5% or 15 million surgical procedures are carried out using spinal anesthesia techniques. The aim of this research is to determine the complications that occur after spinal anesthesia with Sub Arachnoid Block (SAB). The research design used is quantitative analytical descriptive with a cross-sectional approach. The research was conducted in July 2023. Samples were taken using a purposive sampling technique of 57 respondents. The instruments used in this study were measuring hypotension using a bedside monitor, arrhythmia using an oximeter and urine retention using a urine bag. Meanwhile, for PONV, PAS, PDPH, back pain, use an observation sheet. The data processing technique in this research uses univariate analysis. The results showed that the majority of respondents in this study experienced hypotension with 43 (75%) respondents, arrhythmia 38 (66.7%) respondents, PONV 34 (57.6%) respondents, PAS 42 (73.7%) respondents, PDPH 33 (57.9%) respondents, back pain 43 (75.4%) respondents, urinary retention 39 (68.4%) respondents. The conclusion of this study is post-spinal anesthesia complications, namely hypotension, arrhythmia, PONV, PAS, PDPH, back pain and urinary retention. Patients after surgery and using spinal anesthesia are always monitored and observed properly so that post-operative complications with spinal anesthesia are minimal and can be controlled.